2005
DOI: 10.1111/j.1440-1827.2005.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral schwannoma clinically and radiologically mimicking meningioma

Abstract: A case of intracerebral schwannoma (ICS) occurring in a 33-year-old woman is presented. The patient's history of headache, numbness, tingling and the recent development of weakness of the right upper extremity with right facial droop began during pregnancy. Magnetic resonance imaging (MRI) showed a 4 x 2 x 2 cm heterogeneous, gadolinium-enhanced mass at the left frontoparietal junction, with peritumoral edema and a dural-based attachment. During her pregnancy, the mass increased in size. The surgically resecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
(78 reference statements)
1
30
0
Order By: Relevance
“…However, many authors have indicated that there is no pathognomonic sign for intraparenchymal schwannoma, and that it is impossible to distinguish them from other tumors, such as pilocytic astrocytoma, ganglioglioma, pleomorphic xanthoastrocytoma, and dysembryoplastic neuroepithelial tumor, with radiographic evidence only. Large intraparenchymal schwannomas have been mistaken for meningioma or high-grade glioma11,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many authors have indicated that there is no pathognomonic sign for intraparenchymal schwannoma, and that it is impossible to distinguish them from other tumors, such as pilocytic astrocytoma, ganglioglioma, pleomorphic xanthoastrocytoma, and dysembryoplastic neuroepithelial tumor, with radiographic evidence only. Large intraparenchymal schwannomas have been mistaken for meningioma or high-grade glioma11,14).…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebral schwannoma is mostly benign and can be readily cured by surgery2,8,14,15). Typically, the tumor is well demarcated and can be easily dissected from brain parenchyme in most cases2).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, either immunohistochemical or electron microscopic examination is crucial for the differential diagnosis. [23] In our patient, beside typical Antoni A and Antoni B areas, tumor cells were reactive for S100 protein, neuron specific enolase (NSE) and vimentin and negative for GFAP, supporting diagnosis of schwannoma.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, either immunohistochemical or electron microscopic examination is crucial for the differential diagnosis. 21 …”
Section: Discussionmentioning
confidence: 97%